2005
DOI: 10.3354/dao063025
|View full text |Cite
|
Sign up to set email alerts
|

Picoeucaryot alga infecting blue mussel Mytilus edulis in southern Norway

Abstract: During summer 2001, blue mussels Mytilus edulis with abnormal shell growth were collected near Kragerø, southern Norway. The mussels had green spots in their mantle tissues, mainly posteriorly and ventrally, and in the adductor muscle. Mussels from 4 sites had a prevalence of green spots varying from 2 to 71% that correlated well with shell deformities. Histological examination revealed the presence of round or ovoid algae, 0.9 to 1.5 × 1.2 to 2.4 µm, free within haemocytes and in the lesions, characterised by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…The observation of digested algae inside mussel haemocytes aggregating around algal colonies suggests that the mussel can counteract the infections (Gray et al 1999, Mortensen et al 2005. Mortensen et al (2005) reported the presence of green pustules in soft tissues of Mytilus edulis, resembling the earlier descriptions of Coccomyxa parasitica in M. edulis chilensis in the South Atlantic Ocean (Gray et al 1999). This and previous studies on bivalves infested by C. parasitica were, however, only supported by morphological features.…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…The observation of digested algae inside mussel haemocytes aggregating around algal colonies suggests that the mussel can counteract the infections (Gray et al 1999, Mortensen et al 2005. Mortensen et al (2005) reported the presence of green pustules in soft tissues of Mytilus edulis, resembling the earlier descriptions of Coccomyxa parasitica in M. edulis chilensis in the South Atlantic Ocean (Gray et al 1999). This and previous studies on bivalves infested by C. parasitica were, however, only supported by morphological features.…”
Section: Introductionmentioning
confidence: 67%
“…Bootstrap values for major clades are indicated above internodes and correspond to NJ and MP methods, respectively. Bootstrap values < 70% are indicated by hyphens the Gulf of San José, Argentinean Patagonia, Boraso de Zaixso & Zaixso 1979, Bala 1995) and 2 in the North Atlantic Ocean (Flensburg in the Baltic Sea, Meixner 1984; the southern Norwegian coast, Mortensen et al 2005). Algae isolated from the South Atlantic Ocean mussels were reported as Coccomyxa parasitica based on microscopical observations, while the taxonomic position of the others remained unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations